All Days 1997
DOI: 10.4043/8542-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cased Insulated Pipeline Bundles

Abstract: Bottom tow pipeline bundle installations are gaining acceptance in deepwater developments. This is particularly the case where paraffins and hydrates pose a problem, since insulation and heating lines may easily be added inside the buoyancy casing, with less cost impact than in vessel based methods. However, barriers to more extensive use of the bottom towed bundle technique are perceived problems of potential leakage into the outer casing and perceived problems related to the pressurization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Delafkaran, et al [2] conducted analysis of high temperature thermally insulated PIP risers, provided a design methodology. Nock and Bomba [3] discussed the advantages of cased insulated flowline bundles and the possibility of deepwater application. Nelson, et al [4] reported a new insulation method for controlled depth tow method bundle using foamed polyurethane and silica sphere slurry.…”
Section: Introductionmentioning
confidence: 99%
“…Delafkaran, et al [2] conducted analysis of high temperature thermally insulated PIP risers, provided a design methodology. Nock and Bomba [3] discussed the advantages of cased insulated flowline bundles and the possibility of deepwater application. Nelson, et al [4] reported a new insulation method for controlled depth tow method bundle using foamed polyurethane and silica sphere slurry.…”
Section: Introductionmentioning
confidence: 99%